KAJIAN EFEKTIVITAS SOSIALISASI BAHAYA DESTRUCTIVE FISHING DI HULU SUNGAI SERAYU - Muh. Sulaiman Dadiono; Rima Oktavia Kusuma; Ren Fitriadi; Mustika Palupi (Jurnal Perikanan Pantura (JPP), 2021)
This study aims to determine the effectiveness of the socialization of the dangers of destructive fishing in the upstream area of ​​the Serayu River by PSDKP Cilacap in terms of the communication carried out. Aspects that are seen are the form of communication, communication approach, response and level of understanding of the community. This research method is qualitative research using symbolic interaction. Primary data from interviews with correspondence and secondary data obtained from the results of previous studies. This form of communication is carried out by persuasive communication through meetings between related parties and meeting with the public directly. Interactive discussions are held centrally in one location. The focus of the communication approach taken is to the people in the upper reaches of the Serayu River. The response of most of the correspondents is a positive response. According to them, this socialization opens up new knowledge. Meanwhile, a small number of correspondents consider that this destructive fishing hazard socialization event is an inappropriate step if there is no further step. The level of understanding of correspondents is mostly understood in general terms. While a small number of correspondents said they understood a little. The effectiveness of socializing the dangers of destructive fishing after being reviewed from several aspects can be said to be quite effective.